2020
DOI: 10.1111/jth.14762
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐platelet antibodies in childhood immune thrombocytopenia: Prevalence and prognostic implications

Abstract: Background: Anti-platelet antibody testing may be useful for the diagnosis and management of childhood immune thrombocytopenia (ITP).Objectives: Here we aimed to assess the prevalence and prognostic significance of anti-platelet glycoprotein-specific IgM and IgG antibodies. Methods:Children with newly diagnosed ITP were included at diagnosis and randomized to an intravenous immunoglobulins (IVIg) or careful observation group (TIKI trial). In this well-defined and longitudinally followed cohort (N = 179), anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Antibodies were determined by glycoprotein-specific analysis for GP Ib/IX, IIb/IIIa and V using MAIPA, as previously described. [19] The 25 th , 50 th , and 75 th quantiles (Q1-Q3) were 2, 4 and 7 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies were determined by glycoprotein-specific analysis for GP Ib/IX, IIb/IIIa and V using MAIPA, as previously described. [19] The 25 th , 50 th , and 75 th quantiles (Q1-Q3) were 2, 4 and 7 years.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of circulating anti-platelet antibodies was evaluated by monoclonal antibody-specific immobilization of platelet antigens (MAIPA; glycoprotein-specific) as previously described. [19] Lymphocyte subset immune phenotyping was performed in a centralized laboratory by flow cytometry (Sanquin Immunodiagnostics), using multicolour staining (BD Biosciences; Vianen, The Netherlands; #644611) in TruCount tubes (BD Biosciences #340334) on heparinized whole blood. Thrombopoietin was measured using an in-house ELISA [20,21] and expressed in arbitrary units (AU/mL), where one AU is equal to 9 pg of recombinant TPO (Research Diagnostics, Flanders, NJ, USA).…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…This finding is in accordance with a recent Danish study, in which PA-IgM were significantly more frequent than PA-IgG in children with ITP (63% vs. 44%, P = 0.03) ( 15 ). Schmidt et al have also reported that anti-platelet antibodies were predominantly of the IgM class in children with newly diagnosed ITP ( 16 ). In the same study, the authors have noted that IgM responses were present short term without evidence of class-switching to IgG ( 16 ).…”
Section: Discussionmentioning
confidence: 96%
“…Schmidt et al have also reported that anti-platelet antibodies were predominantly of the IgM class in children with newly diagnosed ITP ( 16 ). In the same study, the authors have noted that IgM responses were present short term without evidence of class-switching to IgG ( 16 ). Such responses are likely to be triggered by infections, and molecular mimicry may play a central role in the development of self-directed anti-platelet immunity ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation